Kaidah المهر وجوبا خق الشرع وبقاء حق امراة , ماهو مل او منفعة يمكن تسليمها شرعا يجوز التزوج عليها، وما لا لايجوز , الموجب الأ صلي في باب النكاح مهر المثل , متي سمي ما لا يصلح مهرا صح العقد فيه, ووجب مهر المثل dalam Pembahasan Mahar - Laila Suhada; Mhd Amar Adly; Heri Firmansyah (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2024)
This article explains the rules of dowry which is a form of seriousness of a prospective husband towards the prospective wife he is going to marry. This paper uses the library research method which refers to previous research and also from books related to dowry. With the aim of finding out about the dowry and the rules of jurisprudence related to the dowry. The rules include that the dowry is obligatory and is a woman's right. The initial requirement in the marriage section is a commensurate dowry, property or benefits that can be handed over legally, marriage can be given to it and nothing that is not allowed, then what is not considered a dowry is called dowry, then the contract is valid and a similar dowry is required.